2022
DOI: 10.3390/ijerph19042322
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Social Support between Loneliness and Depression: Differences between the Young-Old and the Old-Old

Abstract: This study aimed to investigate the moderation of social support in the association between loneliness and depression in different age groups of older adults. The sample consisted of 1532 community-dwelling adults aged 65 years or older, based on the data from the National Social Life, Health, and Aging Project (NSHAP), Wave 3 (2015–2016). Eleven items of the Center for Epidemiologic Studies Depression Scale (CES-D) were used to measure depressive symptoms. Similarly, a four-item scale was used to measure soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…This was consistent with Shen et al's study, who encouraged older adults to participate in social activities and build good interpersonal relationships [114]. The presence of loved ones (such as a spouse or children) with older adults plays an important role in maintaining good mental health [115]. Numerous studies have confirmed that older men receive more support from their wives and report greater satisfaction [116,117]; more-over, older women receive feelings of well-being when they receive support from children or friends [118].…”
Section: Discussionsupporting
confidence: 87%
“…This was consistent with Shen et al's study, who encouraged older adults to participate in social activities and build good interpersonal relationships [114]. The presence of loved ones (such as a spouse or children) with older adults plays an important role in maintaining good mental health [115]. Numerous studies have confirmed that older men receive more support from their wives and report greater satisfaction [116,117]; more-over, older women receive feelings of well-being when they receive support from children or friends [118].…”
Section: Discussionsupporting
confidence: 87%
“…A growing body of literature acknowledges that experience in aging in place varies at different stages of later life [ 25 , 26 , 27 ]. The pathways linking POS and well-being are likely to differ between young-old and old-old groups.…”
Section: Literature Review: From Pos To Multifaceted Well-beingmentioning
confidence: 99%
“…A British study suggested that the sense of familiarity and social connections with the place of residence contributes to place attachment [ 24 ]. However, existing studies seem to pay insufficient attention to mechanisms underlying the linkages between people’s environmental encounters and well-being, especially mechanisms at people’s different life stages [ 22 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some cultures or communities, it is thought that the larger the family, the more blessed the family is. Besides, larger families may provide more opportunities for social support and caregiving, which can benefit mental health [ 10 , 15 , 71 ].…”
Section: Discussionmentioning
confidence: 99%